Alloy design and fabrication of ingots in Cu-Zn-Mn-Ni-Sn high-entropy and Cu-Zn-Mn-Ni medium-entropy brasses. (5th November 2019) - Nagase, Takeshi; Shibata, Akihiro; Matsumuro, Mitsuaki; Takemura, Mamoru; Semboshi, Satoshi
Abstract: Cu-Zn-Mn-Ni-Sn high-entropy (HE) and Cu-Zn-Mn-Ni medium-entropy (ME) brasses were designed and the ingots were fabricated by conventional casting process via metallic mold casting. The ingots of the equiatomic CuZnMnNi ME brass showed dendrite structures composed of body-centered-cubic (BCC) and face-centered-cubic (FCC) phases. A single FCC phase was obtained in the ingots of non-equiatomic Cux ZnMnNi ( x  = 2, 3, and 4) ME brasses. The addition of Sn to Cu x ZnMnNi ( x  = 1, and 2) ME brasses significantly affected the solidification microstructure and the constituent phases. The ingots of the CuZnMnNiSn0.2 HE brass showed only sharp peaks corresponding to BCC phase in XRD patterns. The Sn addition to Cu x ZnMnNi ( x  = 1, and 2) ME brasses led to superior mechanical strength in the ingots. Graphical abstract: Unlabelled Image Highlights: High-entropy (HE) and medium-entropy (ME) brasses were developed. Cu-Zn-Mn-Ni ME brasses and Cu-Zn-Mn-Ni-Sn HE brasses were designed. The alloy map for the effects of Sn and Cu concentration was constructed. Equiatomic CuZnMnNi ME brass shows a dendrite structure with BCC and FCC phases. A single FCC phase was obtained in Cu x ZnMnNi ( x  = 2, 3, and 4) ME brasses. XRD results show only sharp peaks corresponding to the BCC phase for CuZnMnNiSn0.2 .